EVALUATION OF PHYTOCONSTITUENTS, IN VITRO ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF AGARICUS BISPORUS - Senthilkumar, V.; Sathishkumar, G.; Sivaramakrishnan, S.; Sujatha, K.; Razia, M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was aimed to investigate the phytochemicals, antimicrobial and antioxidant potential of wild edible mushroom (Agaricus bisporus). Methods: Initially, phytochemical screening was carried out to identify the major phytoconstituents present in A. bisporus. Fourier transform infrared spectroscopy (FTIR) and GC-MS analysis were executed to study the phytochemical profile of A. bisporus methanolic extract. On the other hand, in vitro antioxidant activity was evaluated by reducing power assay and H2O2 scavenging assay. Also, Antibacterial activity was assessed by the agar-well diffusion method. Results: The total phenol content was found to be 5.8 mg GAE/g in aqueous extract and 7.4 mg GAE/g in the methanolic extract of A. bisporus. Antioxidant assays clearly indicate that the methanolic extract of A. bisporus displays highest H2O2 scavenging activity than aqueous extract. The methanolic extract of A. bisporus gave a higher reducing power than the aqueous extract depicts its antioxidant potential. Similarly, methanolic extract of A. bisporus gives excellent antimicrobial activity against tested human pathogens whereas aqueous extract showed comparatively less action. A Higher level of the zone of inhibition was measured against P. aureginosa and S. aureus whereas E. coli and B. subtilus displayed a moderate level of inhibitory action. Conclusion: The overall results suggest that methanolic extract of A. bisporus has shown stupendous antioxidant and antimicrobial potential. This study can be useful to develop commercially viable natural drugs for biomedical applications. Keywords: Agaricus bisporus, GC-MS analysis, Antioxidant, Human pathogens, Phenolic compounds.